Large deformation of metallic hollow spheres - Speich, Marco (Trans Tech Publications Ltd., 2009)
Hollow sphere structures are a new group of advanced lightweight materials for multifunctional applications. Within the scope of this paper, the uniaxial deformation behaviour in the regime of large deformations is investigated. Appropriate computational models are developed to account for the deformation mechanisms occurring under high deformations. Macroscopic stressstrain curves are derived and the influence of different material parameters is investigated.